Outcome of Surgical Management of Sacrococcygeal Pilonidal Sinus Disease with Rotation Flap in 52 Patients—A Retrospective Study - Abbas Mistry; Parvez Shaikh; Aizaz Mohammed; Samir Bagasrawala; Ankit Chauhan; George Anthony (Indian Journal of Plastic Surgery, 2021)
Background Surgical treatment of sacrococcygeal pilonidal sinus disease (SPSD) consists of radical excision of the entire tract and treatment of the resultant raw area. Here, the authors have reviewed the results of the rotation flap for closure of the SPSD. Aim This study aims to evaluate the outcomes following SPSD excision and rotation flap closure. Materials and Methods All patients were treated for SPSD with excision and closure using a rotation flap from January 2010 to September 2018. Cases having a follow-up of at least 6 months post surgery were evaluated. Result A total of 52 patients were included in the study; 42 cases were of primary disease while 10 were of recurrent disease. The patients’ follow-up records on the 3rd day, 10th day, 1 month, and 6 months were evaluated. None of the patients showed any signs of recurrence on follow-ups. One patient developed a hematoma on the third day post surgery which was treated conservatively. One patient developed a seroma in the perianal region on the fifth postoperative day which required aspiration. Both these patients healed well subsequently. Conclusion Rotation flap is a (simple and reliable) treatment option for closure of postexcision SPSD defect. It not only takes the tension away from suture line, but also pushes the gluteal fat from the sides into the midline, obliterating the deep crevice of the natal cleft which is believed to be one of the important factors in the causation of SPSD, thus minimizing recurrence.